2012
DOI: 10.1002/hon.2017
|View full text |Cite
|
Sign up to set email alerts
|

The dog as a possible animal model for human non‐Hodgkin lymphoma: a review

Abstract: Lymphoma represents the most frequent hematopoietic cancer in dogs, and it shows significant overlap with the human disease. Several environmental factors have been associated with canine lymphoma, suggesting that they may contribute to lymphomagenesis. Canine lymphoma often presents in advanced stage (III-V) at diagnosis and, most commonly, has an aggressive clinical course requiring prompt treatment, which relies on the use of polychemotherapy. In this review, we will summarize the state-of-the-art of canine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
149
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(159 citation statements)
references
References 78 publications
2
149
0
8
Order By: Relevance
“…This suggests that, as some previous studies have suggested, the domestic dog is an ideal model for understanding human cancer (Marconato, Gelain & Comazzi, 2013; Rowell, McCarthy & Alvarez, 2011). However, when we analyzed the specific types of neoplasia associated with death in the two species, we found significant differences.…”
Section: Discussionmentioning
confidence: 62%
“…This suggests that, as some previous studies have suggested, the domestic dog is an ideal model for understanding human cancer (Marconato, Gelain & Comazzi, 2013; Rowell, McCarthy & Alvarez, 2011). However, when we analyzed the specific types of neoplasia associated with death in the two species, we found significant differences.…”
Section: Discussionmentioning
confidence: 62%
“…Lymphoma is the most common haematopoietic malignancy in dogs, constituting up to 83% of cases (11). The main method of treating systemic malignancies like leukaemia and lymphoma is chemotherapy, because it elicits an initial response in the majority of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Dogs may be the most relevant animal model to study new therapies for this indication. Actually, naturally occurring lymphomas in dogs are closer to their human counterparts than any xenograft mice models, because of their growth over long periods of time in an intact immune system, interindividual and intratumoral heterogeneity, development of recurrent or resistant diseases, and metastasis (13). Clinical presentation, biologic behavior, tumor genetics, and treatment response are very similar between canine and human DLBCL (14,15).…”
Section: Introductionmentioning
confidence: 99%